Validation of a Non-Specific Dye Real-Time PCR Assay for Porcine Adulteration in Meatball Using ND5 Primer - Tri Joko Raharjo; Ery Nourika Alfiraza; Esti Enjelina; Deni Pranowo (Universitas Gadjah Mada, 2017)
Porcine adulteration in meatball samples were analyzed using real-time polymerase chain reaction (RT-PCR), based on the ND5 primer obtained by previous study. This work consisted of three stages which were annealing temperature optimization, method validation, and application. DNA template was extracted using phenol-CIAA (chloroform-iso amyl alcohol) method. The optimum annealing temperature for ND5 primers (forward primer 5'-CATTCGCCTCACTCACATTAACC-3' and reverse primer 5'-AAGAGAGAGTTCTACGGTCTGTAG-3') was 58.0 °C, obtained after testing annealing at 50.5 to 59.5 °C gradient temperature with 5 °C interval. Melting curve analysis was done at 65.0 to 95.0 °C, with increasing temperature for 0.5 °C per 2 sec. Method was validated for its specificity, precision and limit of detection. RT-PCR method with ND5 primers produced 227 bp DNA fragment with 78.50 °C Tm value. From eight commercial meatball samples, one was detected containing porcine. The methods showed high specificity and precision, with experimentally determined limits for porcine were no less than 1%.